2020
DOI: 10.1002/csc2.20225
|View full text |Cite
|
Sign up to set email alerts
|

Differences in proteome response to cold acclimation in Zoysia japonica cultivars with different levels of freeze tolerance

Abstract: Zoysiagrasses (Zoysia spp.) are warm‐season turfgrasses primarily grown in the southern and transition zones of the United States. An understanding of the physiological and proteomic changes that zoysiagrasses undergo during cold acclimation may shed light on phenotypic traits and proteins useful in selection of freeze‐tolerant genotypes. We investigated the relationship between cold acclimation, protein expression, and freeze tolerance in cold acclimated (CA) and nonacclimated (NA) plants of Zoysia japonica S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…However, opposite results were shown without CA: Victoria had higher values for both SGT and RG than Meyer (Table 1, Supplemental Figure S1). In another recent study, we found the LT50 value (the temperature at which 50% of the plants die) of CA Meyer was significantly lower than CA Victoria, but NA cultivars were similar to each other (Brown et al., 2020). These results indicate that although Victoria shows more constitutive freezing tolerance that is less dependent on the strength of CA, Meyer exhibits higher levels of CA that play a significant effect on improving freezing survival.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, opposite results were shown without CA: Victoria had higher values for both SGT and RG than Meyer (Table 1, Supplemental Figure S1). In another recent study, we found the LT50 value (the temperature at which 50% of the plants die) of CA Meyer was significantly lower than CA Victoria, but NA cultivars were similar to each other (Brown et al., 2020). These results indicate that although Victoria shows more constitutive freezing tolerance that is less dependent on the strength of CA, Meyer exhibits higher levels of CA that play a significant effect on improving freezing survival.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, Brown et al. (2020) reported that CA accounted for a 1.9‐fold increase in zoysiagrass survival compared with the non‐acclimation (NA) treatment in a controlled environment freezing test. Further proteomic analysis in zoysiagrass identified 62 differentially accumulated proteins under CA, which were involved primarily in transcription, signal transduction and stress defense, carbohydrate and energy metabolism, and protein and amino acid metabolism (Brown et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that substance accumulation guarantees overwintering success and the revival of plants ( Wang et al., 2019 ). Plants usually accumulate soluble sugar to tolerate cold stress in winter ( Brown et al., 2020 ), as well as accumulate soluble protein to support enzyme synthesis, dormant bud occurrence, and subsequent revival in spring ( Brown et al., 2020 ). In this study, the substance accumulation of L. japonica was reflected in the increased biomass ( Table 1 ) and the increased contents of soluble sugar and protein of the roots, even after the leaves withered by week 6 ( Figures 4A , 5A ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanins may scavenge ROS as an efficient antioxidant by neutralizing radicals with their hydroxyl groups to preserve normal cellular redox homeostasis; hence, plants often generate anthocyanins to reduce oxidative damage caused by low-temperature stress [ 20 , 21 , 22 , 23 , 24 , 25 ]. Low-temperature responsive networks in zoysiagrass have been investigated through physiological, biochemical, molecular, genetic and omic approaches [ 7 , 15 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. However, no studies have attempted to associate anthocyanin accumulation with cold tolerance in zoysiagrass.…”
Section: Introductionmentioning
confidence: 99%